Comparing the size of the U.S. and chinese economies : will China overtake the United states? - Пашкова, Ю. І.; Pashkova, Yu. I. (Харків : Харкiвський нацiональний унiверситет iмені В. Н. Каразiна, 2012)
The article analyzes the comparative size of the U.S. and Chinese economies using nominal GDP and purchasing power parity (PPP) indicators. It examines China’s economic growth dynamics and its transformation from a centrally planned economy into one of the world’s leading economies. The study considers international forecasts regarding China potentially surpassing the United States in economic size, as well as the implications of this process for the global economy and individual countries, including Ukraine.

У статті проаналізовано порівняльні розміри економік США та Китаю з використанням номінального ВВП та показників за паритетом купівельної спроможності (ПКС). Розглянуто динаміку економічного зростання Китаю, його трансформацію з планової економіки в одну з провідних світових економік. Досліджено прогнози міжнародних організацій щодо можливого випередження США за розміром економіки, а також наслідки цього процесу для глобальної економіки та окремих країн, зокрема України.
Keywords: SOCIAL SCIENCES::Business and economics::Economics; Gross Domestic Product (GDP); purchasing power parity; China; United States; global economy; Валовий внутрішній продукт (ВВП); паритет купівельної спроможності; Китай; США; глобальна економіка